A numerical study of nighttime ionospheric variations in the American sector during 28–29 October 2003. Issue 9 (16th September 2016) - Chen, Xuetao; Lei, Jiuhou; Wang, Wenbin; Burns, Alan G.; Luan, Xiaoli; Dou, Xiankang
Abstract: Variations of nighttime F 2 peak height ( hm F 2 ) over the American sector during the 28–29 October 2003 storm period were investigated using the National Center for Atmospheric Research Thermosphere‐Ionosphere Electrodynamics Global Circulation Model. The model was generally able to reproduce the ionospheric variations on 28–29 October 2003 observed by the ionosondes. A series of controlled model simulations were subsequently undertaken to examine the effects of electric fields and neutral winds on the ionosphere. The numerical experiments suggest that the dramatic nighttime increase of hm F 2 on the storm day 29 October is mainly caused by traveling atmospheric disturbances (TADs) from the high latitudes of the Northern Hemisphere. However, the electric field plays an important role in causing the elevation of hm F 2 in the equatorial region. The prompt penetration electric field (PPEF) associated with the southward component of the interplanetary magnetic field ( Bz ) is westward on the nightside, whereas when Bz reverses and becomes northward, the PPEF is westward in the premidnight and turns to eastward in the postmidnight. These PPEFs greatly affect the low‐latitude ionosphere during storm time. On 28 October, even though the Bz disturbance was weak with a short duration of southward Bz, the TADs from the Southern Hemisphere can propagate to the Northern Hemisphere and result in the corresponding oscillations in the nightside hm F 2 . Key Points: The effects of neutral winds and PPEFs on the nighttime ionosphere during 28–29 October 2003 were investigated The disturbances of the nighttime ionosphere in this event were mainly caused by TADs when the magnetic activity was weak Eastward PPEF with northward Bz contributed to the uplifting of the nighttime ionosphere at low latitudes on 29 October